To what extent do circumstances affect the nature of actions? - Moń, Ryszard (Studia Philosophiae Christianae, 2017)
The author of this article discusses the relationship between the subject matter (contents) of an action and the circumstances in which it is performed. The related problems were one of the motives behind John Paul II’s encyclical "Veritatis Splendor". He attempts to show the essence of this problem with reference to Thomas Nagel’s book "The View From Nowhere". Contemporary thinkers, however, those referred to as consequentialists or proportionalists, believe that circumstances are in fact part of the physical act itself and materially affect its understanding. Referring to that principle in "Veritatis Splendor", John Paul II says that he is aware one must often choose between actions that are inherently evil, but he believes that this is permissible only when there are no alternatives to choose instead. One should never choose an evil action to achieve a positive effect, or do that because the proportion of positive effects is greater than that of negative ones. The author shows also a striking similarity between what John Paul II wrote about the absolute character of moral norms and the external nature of circumstances with respect to the essence of the act, its internal purpose, and what we read in "The View from Nowhere", a book by Thomas Nagel, who considers himself an atheist. The search for objectivity in moral judgment is difficult, but not impossible, at least as far as its essence is concerned. Failure to consider the relevance of reasons to persons, and failure to make that reference, but first of all the treatment of circumstances as part of a moral action turns ethics into praxeology, or a theory of efficient action.